A Comparative Analysis of Media Viability between Bantay Balita and Dateline Weekly Newspaper in the Digital Age of Journalism - Ongue, Ann Marie Vera S.; Tarrobago, Rocellen E.; Gomez, Abigail C.; Cabrito, Joshua (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study aimed to analyze the survival of two operational community newspapers in Cavite: Bantay Balita and Dateline Weekly Newspaper, amidst the surge of the digital age of journalism. The researchers employed a qualitative method, specifically a descriptive type, through semi-structured interviews for the research design. Purposive and convenience sampling techniques were utilized in the study. The selected editorial board members of Bantay Balita and Dateline Weekly Newspaper were the main criteria for participant selection. During data analysis, the researchers examined the gathered data using thematic analysis. In this method, researchers interpreted the extracted codes from participants’ responses. The results revealed that Dateline Weekly Newspaper is more stable than Bantay Balita due to its long-standing presence, digital adaptability, additional business opportunities, and strong networks with accredited partners, substantially contributing to its survival. Dateline maintains a good reputation, is free from lawsuits and criticism, and actively avoids competition. However, it faces challenges in the editorial process, production, and distribution resources. It is observed that Dateline Weekly Newspaper lacks the ABCs of news writing—accuracy, brevity, and clarity—in some of its news articles, often relying on outsourced press releases and encountering issues with operators and delivery systems. On the other hand, Bantay Balita struggles with digital adaptation but remains viable due to its quality journalism. Most of its connections are with governmental sectors, limiting its business potential. Despite legal accusations and financial distress, Bantay Balita continues to operate by engaging in friendly competition, contributing to its resilience in the industry.